Breast cancer in systemic lupus erythematosus (SLE): receptor status and treatment. (January 2018) - Chan, K; Clarke, A E; Ramsey-Goldman, R; Foulkes, W; Tessier Cloutier, B; Urowitz, M B; Gladman, D; Nived, O; Romero-Diaz, J; Petri, M; Ginzler, E; Fortin, P R; et al.
Objective: There is a decreased risk of breast cancer in systemic lupus erythematosus (SLE) versus the general population; little is known regarding the receptor status of breast cancers in SLE, or treatment. Methods: Breast cancer cases occurring after SLE diagnosis were ascertained through linkage with tumor registries. We determined breast cancer positivity for estrogen receptors (ER), progesterone receptors (PR), and/or Human Epidermal Growth Factor Receptor 2 (HER2), as well as cancer treatment. Results: We obtained information on ER, PR, and/or HER2 status for 63 SLE patients with breast cancer. Fifty-three had information on ER and/or PR status; 36 of these (69%) were ER positive. Thirty-six of the 63 had information on HER2 status; of these, 26 had complete information on all three receptors. Twenty-one of these 26 (81%) were HER2 negative; seven of 26(27%) were triple negative. All but one patient underwent surgery; 11.5% received both non-tamoxifen chemotherapy and radiotherapy, 16.4% radiotherapy without non-tamoxifen chemotherapy, and 14.7% received non-tamoxifen chemotherapy without radiotherapy. Conclusion: ER positivity was similar to historical general population figures, with a trend toward a higher proportion of triple-negative breast cancers in SLE (possibly reflecting the relatively young age of our SLE patients).